Co‐optimization of SnS absorber and Zn(O, S) buffer materials for improved solar cells. (5th May 2014) - Park, Helen Hejin; Heasley, Rachel; Sun, Leizhi; Steinmann, Vera; Jaramillo, Rafael; Hartman, Katy; Chakraborty, Rupak; Sinsermsuksakul, Prasert; Chua, Danny; Buonassisi, Tonio; Gordon, Roy G.
Abstract Thin‐film solar cells consisting of earth‐abundant and non‐toxic materials were made from pulsed chemical vapor deposition (pulsed‐CVD) of SnS as the p‐type absorber layer and atomic layer deposition (ALD) of Zn(O, S) as the n‐type buffer layer. The effects of deposition temperature and annealing conditions of the SnS absorber layer were studied for solar cells with a structure of Mo/SnS/Zn(O, S)/ZnO/ITO. Solar cells were further optimized by varying the stoichiometry of Zn(O, S) and the annealing conditions of SnS. Post‐deposition annealing in pure hydrogen sulfide improved crystallinity and increased the carrier mobility by one order of magnitude, and a power conversion efficiency up to 2.9% was achieved. Copyright © 2014 John Wiley & Sons, Ltd.